Analysis of member performance: a case of BRAC's rural development programme - Halder, Shantana R.; Husain, A M Muazzam (BRAC, 2019)
A comparative analysis of high performing and other BRAC members has been made to determine factors responsible for differences in their performance. It was found that both the success cases and other members owned similar amount of land at the time of joining BRAC programmes. Among the success group the performances of self employed, literate, and female headed households were significantly higher compared to other members. Members with traits of leadership, higher initial endowment, higher involvement in relatively high return activities, higher entrepreneurial skill and higher social position achieved greater success. The success members also had close kinship ties with other members in the organization. Multiple loan use was also found as one of the influencing/actors behind their success.